THE NIGERIAN FACTOR IN LIBERIAN PEACE PROCESS 1990- 1993 - Olawale, Salami B. (European Scientific Journal, ESJ, 2015)
The outbreak of civil war in Liberia in 1990 put pressure on the stability of the West African sub-region. An in an attempt to manage the crisis and curtail the contagious effect of the war, Nigeria embarked of a peace making process which led to the establishment of the Economic Community of West African Monitoring Group, ECOMOG. Apart from this, Nigeria contributed more than 10,000 troops to the ECOMOG mission and gave other financial and material support to the war torn country. A refugee camp was also established for Liberian refugee in Oru, a suburb of Ijebu-Ode, in Ijebu North Local Government area of Ogun State in South-Western Nigeria. This paper examines among others the role of Nigeria in the Liberian peace process. Drawing from its findings, the paper argues that Nigeria’s involvement in the Liberian peace process was motivated primarily by the need for the ruling military junta in Nigeria to attract external credibility. This however, was achieved at a very great cost in terms of human and material resources.